Sharia Actualization: Realizing the Indonesian Islamic Jurisprudence - Ahmad Ridwan; Siskha Putri Sayekti; Eva Siti Faridah (Hikmatuna : Journal for Integrative Islamic Studies, 2023)
Sharia is intertwined with fiqh. In English terminology, Sharia is translated as “Islamic law based on the Quran.” In the context of reforming Islamic law in Indonesia, the method of talfiq is needed, selectively choosing opinions that align with the conditions in Indonesia. It is believed that the Islamic legal tradition, in terms of formation, reform, or legal development, is closer to the Anglo-Saxon legal system known as precedent law. This is because Muslims fully accept that all the dogma, principles, and Islamic sharia are already perfected in the Quran and the Sunnah of the Prophet. The question at hand is how these legal texts can be guaranteed to remain relevant and capable of meeting the needs of all times, places, cultural contexts, and social levels. This study delves deeper into the Sharia within the Contemporary Era, relating to the Typology of Islamic Legal Reform Actualization and the Application of Islamic Law in Indonesia. The research is a literature study, focusing on the examination of figures and the object of study, which is Sharia in a modern context. This study employed a qualitative approach to analyze the Typology of Islamic Legal Reform Actualization and the Application of Islamic Law in Indonesia. The dynamics of Islamic law in Indonesia are expected to continue evolving and innovating so that in the future, Islamic law with universal value will not only pertain to the realm of fiqh muamalat (transactions) and akhwal sakhsiah (personal matters) but will also contribute positively to the development of national law in Indonesia in various aspects.